The Influence of the Independent Curriculum on Students' Intrapersonal and Interpersonal Intelligence - Setiadi Setiadi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
The purpose of this study is to analyze the influence of the Independent Curriculum (X) on intrapersonal intelligence (Y1) and interpersonal intelligence (Y2) separately and simultaneously. Survey, Simple Linear Regression Analysis and Multivariate Tests were applied to analyze the data. The sampling technique was a census or total technique with 137 respondents. The coefficient sig values for the normality test were 0.087 and 0.200; the linearity test was 0.432 and 0.068; and heteroscedasticity were 0.915 and 0.096. The significance level used was 0.05. First, the significance of the simple linear regression was 0.031 which skewed towards positive with a B value of 0.384. Second, the significance of the simple linear regression was 0.000 which also skewed towards positive with a B value of 0.347. The significance of the Multivariate Test was 0.013. Both analysis results showed that the sig value test <0.05. This means that the Independent Curriculum (X) significantly influences intrapersonal (Y1) and interpersonal (Y2) intelligence separately and simultaneously. The degree of impact of variable X on variable Y1 is 38.4%, and Y2 is 34.7% separately and 30% and 21% simultaneously.